Characteristics of Bacteremia in Pediatric Oncology Patients Based on Pathogen Classification as Associated with the Gastrointestinal Mucosa or Skin. (16th March 2015) - Flagg, Aron; Worley, Sarah; Foster, Charles B.
<x content-type="archive" xml:space="preserve">Abstract</x> Factors favoring blood stream infections associated with gastrointestinal mucosa versus skin organisms were explored. An observed difference was attributable to bacteremia from oral flora in patients with acute myelogenous leukemia or mucositis. Our data do not support the conclusion that isolation of enteric Gram-negatives is unrelated to the central catheter. Infect Control Hosp Epidemiol 2015;00(0): 1–4